Pengaruh Profitabilitas, Modal Kerja, dan Umur Perusahaan Terhadap Nilai Perusahaan: (Studi Empiris pada Perusahaan Sektor Properti & Real estate yang Terdaftar di Bursa Efek Indonesia Periode 2019 – 2022) - Mohamad Farhan Pakaya; Rachmat Arif (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
This study aims to determine the effect of profitability, working capital and company age on firm value in property and real estate sector companies listed on the Indonesia Stock Exchange for the period 2019 - 2022. The data used in this study was obtained from financial report data and annual reports obtained from the IDX and Yahoo Finance websites. The population in this study are property and real estate sector companies listed on the Indonesia Stock Exchange. This research sample used 54 companies in the property and real estate sector. The analysis technique used in this research is a multiple linear regression analysis test using the Statistical Package for the Social Sciences (SPSS) version 22 program. Based on the results of this research, it shows that profitability has a positive and significant effect on company value, while working capital and company age do not influence on firm value.